2013
DOI: 10.1097/mib.0b013e318280b169
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effects of Certolizumab Pegol and Golimumab Mediated by Transmembrane Tumor Necrosis Factor α

Abstract: The cytotoxic effects of anti-TNF-α agents on TNF-α-expressing cells are considered to be associated with the clinical effect of these agents on granulomatous diseases. The direct cytotoxic effect of certolizumab pegol on TNF-α-producing cells may contribute to its clinical efficacy in Crohn's disease. Golimumab may be less effective for granulomatous diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 28 publications
(33 reference statements)
1
36
0
Order By: Relevance
“…Golimumab, however, shows a minor apoptosis activity as compared to adalimumab and infliximab (Ueda et al. 2013; Urbano et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Golimumab, however, shows a minor apoptosis activity as compared to adalimumab and infliximab (Ueda et al. 2013; Urbano et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In both settings, etanercept binding was shown to be low. The more recently approved anti-TNF antibody golimumab induced both CDC and ADCC to a similar extent as infliximab and adalimumab[77]. …”
Section: Antibody-dependent Cellular Cytotoxicity and Complement-depementioning
confidence: 99%
“…35 Evidence exists that infliximab, adalimumab, and golimumab can cause antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). 36 In vitro examination of cells overexpressing mTNF has demonstrated that infliximab and adalimumab induce CDC and ADCC but both processes are reduced upon etanercept administration, which is unable to bind C3, and abrogated under certolizumab pegol administration, which does not have an Fc portion. 37 The efficacy of certolizumab in treatment despite its inability to cause apoptosis calls into question the significance of apoptosis in anti-TNF treatment of IBD, though this is still up for debate.…”
Section: Currently Available Therapiesmentioning
confidence: 99%